Implementation of Curcuma xanthorrhiza Roxb Encapsulation as a Feed Additive on Production Performance of Broiler - dos Santos, Abilio; Indrati, Rositawati; Sjofjan, Osfar (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
The research aim to determine Curcuma xanthorrhiza Roxb encapsulated as a feed additive and its implementation on broiler production performance. The method used was a field experiment using a Completely Randomized Design (CRD), which consisted of 6 treatments and 4 replicates, namely; (P0-) negative control (commercial feed), (P1+) positive control (antibiotic 0.1%), P2 (C. xanthorrhiza encapsulation 0.25%), P3 (C. xanthorrhiza encapsulation 0.50%), P4 (C. xanthorrhiza encapsulation 0.75%) and P5 (C. xanthorrhiza encapsulation 1%). The results showed that the addition of temulawak (Curcuma xanthorrhiza Roxb) encapsulation in broiler feed can have a very significant effect (P < 0.01) on IOFC, a significant effect (P < 0.05) on body weight, feed conversion, and gives no significant effect (P>0.05) on feed consumption and carcass percentage. The use of temulawak (Curcuma xanthorrhiza Roxb) encapsulation at the level of 0.50% in broiler feed, numerically showed positive results on feed consumption, body weight gain, carcass percentage, IOFC and feed conversion. In conclusion, the addition of temulawak (Curcuma xanthorrhiza Roxb) encapsulated at the level of 0.50% in broiler feed is recommended as a feed additive to replace antibiotics because it tends to increase broiler production performance